A Qualitative Analysis of Resilience in Postgraduate Students - Benítez-Corona, Lilia; Barrón-Tirado, María Concepción (Revista Electrónica Educare, 2018)
The development of resilience is acquired through the life experiences of individuals. In this way, the results obtained in postdoctoral research are presented: “The development of resilient competences in graduate students in Pedagogy of the National Autonomous University of Mexico (UNAM)”. Resilience is the ability to live positively despite the adversity or difficult situations faced by people in different social contexts. Given its subjectivity, analyzing turns complex, because difficulties are perceived differently by each individual. The aim of the article is to show the analysis of resilience from the point of view of postgraduate students in order to identify what factors have developed their resilience, how they built it and how it has impacted their training as specialists in educational research. The qualitative methodology was approached through hermeneutics to recognize diversity, understand reality and build meaning from the historical understanding of the symbolic world of the individual, since human behavior can only be understood through meanings. For this reason, the workshop technique was used to let the participants to discover their resilience. The sample consisted of 23 graduate students. The findings showed that the positive interaction, the sense of life and the presence of the significant other encouraged this capacity in some students by favoring critical thinking and conscious self-esteem, necessary protective factors in the training of educational researchers.